The effect of rubber dipping by-product on bitumen properties - Mohamad Khalid, Ruzaini (2013)
Nowadays, there a lot of damaged of road pavement and it become a very serious issue in Malaysia. To minimise the damage of pavement surface and increase durability of flexible pavement, the conventional bitumen needs to be improved with regards to performance related properties. Thus, this study presents of the effect of rubber dipping by-product (RDP) on bitumen properties. RDP is waste material from natural rubber industrial and it is in solid forms. Bitumen grade 80/100 PEN was used in this study. The bitumen was modified with varying percentages of RDP; 0% for control sample, 5%, 10%, 15% and 20% by the total weight of the bitumen with mixing temperature of 180°C, mixing time of 60 minutes and mixing speed of 800rpm. Laboratory tests carried out were penetration, softening point, viscosity, rolling thin film oven (RTFO) and pressure aging vessel (PAV) test based on the ASTM standard. From the result of penetration, viscosity, PI, and PVN in this study, the RDP modified bitumen led to improve bitumen resistance to oxidative aging because addition of RDP increases bitumen properties after RTFO and PAV test compared to unmodified bitumen. Moreover, the additive of RDP can be increased of temperature susceptibility and increased viscosity properties. The findings from laboratory’s result show that sample with 10% RDP performed better compared to other percentages